The deubiquitinase Usp9x regulates PRC2-mediated chromatin reprogramming during mouse development - Trisha A. Macrae (Nature Portfolio, 2021)
During development, H3K27me3 is reallocated from large domains in preimplantation embryos to mark promoters of developmental genes. Here the authors show that the deubiquitinase Usp9x interacts with, deubiquitinates and stabilizes PRC2 and provide evidence that a Usp9x-PRC2 regulatory axis is critical at peri-implantation.